From Virtual to Real: Investigating the Gap Between Virtual Laboratory Learning and Real Laboratory Performance in Animal Physiology - Cita Tresnawati; Fitri Ariyanti (Universitas Lambung Mangkurat, 2026)
This study aims to examine the performance gap between virtual laboratory-based instruction and real laboratory practicum in the Animal Physiology course. The research employed a mixed-methods approach with an explanatory sequential design, in which quantitative data were emphasized. The participants comprised 31 fifth-semester undergraduate students who engaged in two virtual laboratory sessions and two hands-on laboratory sessions conducted without additional instructor explanation. Laboratory performance was assessed across six dimensions of laboratory skills. The results indicate that procedural and psychomotor skills were in the moderate category, whereas data analysis, drawing conclusions, and presentation skills were in higher categories. Qualitative findings corroborate that virtual laboratories are effective in strengthening conceptual understanding, data literacy, and scientific communication; however, they are less effective in transferring technical and procedural skills to authentic laboratory contexts. Limited physical interaction with equipment, minimal sensorimotor feedback, and contextual discrepancies between simulation and real practice were identified as the primary contributing factors. This study concludes that virtual laboratories should be positioned as pre-laboratory scaffolding to support cognitive preparation rather than as substitutes for direct hands-on practicum. The implications of this study indicate that the integration of virtual laboratories and real laboratory practice should be designed complementarily so that the strengthening of conceptual understanding can be followed by the optimal development of students’ procedural and psychomotor skills.